The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/02640414.2012.682082
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Elbow Extension and Elbow Hyperextension in Cricket Bowling: A case study of Jenny Gunn

Abstract: Citation: KING, M.A. and YEADON, M.R., 2012. Quantifying elbow extension and elbow hyperextension in cricket bowling: a case study of Jenny Gunn. Journal of Sports Sciences, 30 (9), pp. 937 -947. AbstractIn this study a method for determining elbow extension and elbow abduction for a cricket bowling delivery was developed and assessed for Jenny Gunn who has hypermobility in both elbows and whose bowling action has been repeatedly queried by umpires. Bowling is a dynamic activity which is assessed visually in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 17 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…Elbow extension is usually limited by the tension in the anterior joint capsule and flexor muscles and to some extent in the anterior parts of the collateral ligament (Palastanga et al, 2002). It is speculated that during fast bowling the load on the elbow can cause elbow hyperextension to occur (Ferdinands and Kersting, 2004;Portus et al, 2006) with peak hyperextension angles reported in excess of 20° (King and Yeadon, 2012). The results of these investigations into the effect of elbow extension on ball speed suggest that there appears to be a relationship between elbow extension and ball release speed (Portus et al, 2006;Roca et al, 2006).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Elbow extension is usually limited by the tension in the anterior joint capsule and flexor muscles and to some extent in the anterior parts of the collateral ligament (Palastanga et al, 2002). It is speculated that during fast bowling the load on the elbow can cause elbow hyperextension to occur (Ferdinands and Kersting, 2004;Portus et al, 2006) with peak hyperextension angles reported in excess of 20° (King and Yeadon, 2012). The results of these investigations into the effect of elbow extension on ball speed suggest that there appears to be a relationship between elbow extension and ball release speed (Portus et al, 2006;Roca et al, 2006).…”
Section: Introductionmentioning
confidence: 64%
“…Secondly, to quantify the maximum effect of elbow hyperextension on ball release speed, an optimisation was run where the torsional spring parameters and , were varied using the Simulated Annealing algorithm (Corana et al, 1987) in order to maximise ball release speed. A penalty was imposed if peak elbow hyperextension exceeded an upper bound of 25° based on previous research (King and Yeadon, 2012). Thirdly to investigate the relationship between the magnitude of elbow hyperextension and ball release speed simulations were required with different elbow hyperextension angle-time histories.…”
Section: Simulations Investigating the Effect Of Elbow Hyperextensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eftaxiopoulou, Gupte, Dear and Bull (2013) found that a triad close to the elbow produced more repeatable results than a mid-arm marker triad. Alternative marker placements were described by King and Yeadon (2012) in which pairs of markers were positioned across the shoulder, elbow and wrist. These upper arm marker placements were chosen in order to be as far away as possible from the soft tissue movement in the central upper arm.…”
Section: Introductionmentioning
confidence: 99%